2019
DOI: 10.1016/j.sapharm.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding older adults' medication decision making and behavior: A study on over-the-counter (OTC) anticholinergic medications

Abstract: A conceptual model of OTC medication purchase and use is presented. Drawing on study findings and behavioral theories, the model depicts dual processes for OTC medication decision making - habit-based and deliberation-based - as well as the antecedents and consequences of decision making. This model suggests several design directions for consumer-oriented interventions to promote OTC medication safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 66 publications
0
22
0
1
Order By: Relevance
“…To analyze card sort data, we used a descriptive method demonstrated in another study where card sort data were intended to probe the participants further and supplement interview and observation data [39]. We calculated the percent of participants sorting each of the eight information cards into "low," "medium," and "high" categories.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze card sort data, we used a descriptive method demonstrated in another study where card sort data were intended to probe the participants further and supplement interview and observation data [39]. We calculated the percent of participants sorting each of the eight information cards into "low," "medium," and "high" categories.…”
Section: Resultsmentioning
confidence: 99%
“…A critical factor at the in-store pharmacy is the pharmacist’s perceived and actual availability to speak, in person and by phone (#11). Holden and colleagues [ 80 ] observed that shoppers sought product information primarily, if at all, from packaging and more rarely (10% of shoppers) from a pharmacist. The ‘embarrassment and ignorance that it was appropriate to seek information from pharmacists’ reported in 1996 [ 81 ] may still be widespread.…”
Section: Participant Roles and Relationships Activities And Actiomentioning
confidence: 99%
“…[51][52][53][54] A recent study examining older adults' medication decision making and behavior in regards to the use of anticholinergic over-the-counter medications found that while seniors were concerned about adverse drug events, they were not aware of age-related risk associated with the use of anticholinergic medications. [55] Anticholinergic agents are used at end-of-life (EOL) for relief of nausea in those with a vestibular component and more commonly, to provide symptomatic relief of excessive secretions. However, data is lacking to support the use of these drugs for this latter indication.…”
Section: Deprescribingmentioning
confidence: 99%